Challenges towards Sustainable Energy as a Substitute for Fossil Fuels for the Case of Municipal Waste Management - Owusu, Prince Appiah; Borkloe, Julius Kwame; Mahamud, Yussif (Journal of Earth Energy Science, Engineering, and Technology, 2024)
The potential in energy generation from municipal waste management (MSW) has great gains in low-income communities in terms of promoting healthy living conditions, attenuating global warming potential (GWP), and enhancing environmental sustainability. The use of waste-to-energy system (WtES) for MSW conversion into renewable energy resources in Ghana has great prospects at Asokore Mampong Municipality. The study put together WtES options in anaerobic digestion and thermochemical for energy potential and compared their GWP and greenhouse gases (GHGs) with those originating from fossil fuel. Thermochemical energy recovery of MSW was estimated to provide 4.24×104 kWh/day and 1.6×104 MWh/year of electricity, equivalent to 1.3295 kilotonnes of oil equivalent (ktoe) and 8.2% of the power requirement for the Municipality in 2021. The anaerobic potential of energy recovery of 55% of the organic fraction of MSW was estimated to provide a biogas production potential (BGrp) estimate of 2.54×106 m3/year and 5.65×107 MJ of thermal heat energy per annum which translates to 5.5 ×103 MWh/year and equivalent of 0.472 Ktoe. In terms of GWP, thermochemical and anaerobic energy recovery generated 24 kg and 3.3 kg of CO2 equivalent (CO2e) for every ton of MSW. There are 302 g and 115 g of CO2e for each kWh of electricity produced through thermochemical and anaerobic recovery respectively. Fossil fuels; natural gas, oil, and coal produce CO2e range of 290 – 930 g CO2e /kWh, 510 – 1170 g CO2e /kWh, and 740 – 1689 g CO2e /kWh respectively. This makes WtES better in terms of GWP. The energy recovery from thermochemical and anaerobic processes is key in managing MSW in low-income communities for a sustainable environment. The strategy has the potential to unravel the complications in overwhelming MSW management which has implications for environmental health hazards, soil and water pollution. The global fight towards GHG reduction from fossil fuels could have a positive impact through the furtherance of the concept used. For successful WtES facilities and benefits to low-income dwellers like Asokore Mampong Municipality in Ghana, strong engineering judgment and technical competence are necessary and this requires collaboration with all stakeholders. Proper management of MSW energy value chain and intervention therefore has the potential for the provision of employment opportunities and economic sustainability in developing economies.